Self-Organization of Student Youth under Conditions of Social Uncertainty - Hoian, Ihor; Yakovleva, Svitlana; Hulias, Inesa; Fomina, Iryna (Kherson State University, 2024)
Theaim is a theoretical and empirical research of the psy-chological characteristics and types of self-organization among student youth in conditions of social uncertainty. Methods. The sample consisted of students from three levels of higher education who were studying at universi-ties in Ukraine, a total of 362 individuals (M = 22.86; SD = ±2.84).An important criterion that united the subjects is that, during the martial law all of them found themselves in a difficult social situation, and their living and study-ing underwent significant spatiotemporal and content changes. Psychodiagnostic methods that were validated by psychologists on Ukrainian samples were used. The main dimensions of readiness for change, self-organi-zation, and self-regulation were determined by: “Read-iness to Change Questionnaire” (RCQ) (Rollnick et al., 1992); “Self-Organization of Activity Test-Questionnaire” (SOATQ) (Mandrikova, 2010); and the questionnaire “Style of Behavior Self-Regulation” (SBSR) (Morosanova, 1991). Results. Twenty-five statistically significant correlations (p < .050; p < .010; p < .001) were identified, demonstrat-ing regular dependencies among the researched parame-ters. Through cluster analysis using the k-means method, four types of self-organization among student youth in conditions of social uncertainty were established: “Adven-turous self-organization” (AS) (Cluster1, n = 47; 12.98%); “Optimistic self-organization” (OS) (Cluster 2, n = 143; 39.50%); “Passionate self-organization” (PS) (Cluster3,n = 97; 26.80%) and “Tolerant self-organization” (TS) (Cluster4, n = 75; 20.72%). Discussionandconclusions.It was substantiated that “adventurousness”, which has the strongest direct correlation with “purposefulness” (R = .231; p < .001), is dangerous. It is explained that a high level of purposefulness and constructive ambition, which is characteristic of student organization leaders, defi-nitely borders on adventurousness, with youthful maxi-malism and can bring record results and feats, as well as have reverse consequences and deep disappointments. It is substantiated that “AS” and “PS” are destructive, while “OS” and “TS” are constructive types of self-organiza-tion. It is summarized that the outlined types represent a successful attempt at clustering the empirical data with the aim to discover new knowledge. It is recommended that the obtained results be implemented in the structural units of higher education institutions that work with stu-dent youth.
Keywords: self-organization; motivation; resilience; values; gender; inclusive educational environment; self-actualization